Consecutive aqueous extractions of wet-milled corn germ cake - Kalman, G. (Array, 2008)
Corn germ cake is an abundant and inexpensive residue of corn germ pressing. The permanent increase of corn processing – due to the recent growing demand for bioethanol– has resulted in a surplus of this by-product, making it unmarketable as feed. Our goal was to find an alternative way to utilize this by-product. We could successfully extract 86 % of the polysaccharide content of the squeezed germ by using only hot distilled water and 1 % dilute sulphuric acid consecutively. The 14.7 % oil content of the squeezed germ was concentrated to 46.25 % in the remaining solid fraction, which is high enough to be pressed.(Oil content of less than 20 % can only be extracted with organic solvents, which is not attractive for food safety and environmental reasons.) The sterol concentration of this oil was 8200 mg kg–1, which is significantly more than the sterol.